Adolescence and andrologist: An imperfect couple - Soraya Olana; Rossella Mazzilli; Michele Delfino; Virginia Zamponi; Cristina Iorio; Fernando Mazzilli (Archivio Italiano di Urologia e Andrologia, 2018)
Objective: The aims of this research were to study: a) the prevalence of male adolescents, aged between 10 and 19 years of age, referred to our Unit for an andrological assessment; b) the reasons (stated and subsequently modified) for referral; c) the prevalence of clinically diagnosed diseases. Materials and methods: A total of 2.855 subjects, referred to the Andrology Unit for a first examination, were retrospectively studied. For each adolescent, a medical history was taken and an andrological physical examination was carried out. Results: Prevalence was found to be 6.9% (197/2855). Subjects were divided into two groups according to age (A: ≤ 14 and B: ≥ 15 years). The original reason stated for their consultation was corrected by 11.7% of the subjects (23/197); this correction concerned almost all the Group B subjects (21/23 (91.3%) vs 2/23 (8.7%) of Group A; p < 0.01). Regarding sexual dysfunctions, a simple explanation of certain conditions reassured the subject in about 15% of the cases. Furthermore, the physical examination proved extremely useful, revealing clinical alterations in more than 60% of subjects. Conclusions: In conclusion, to date in Italy, the prevalence of adolescents among males referred to an Andrology Unit for assessment is very low. It is important to encourage adolescents to undergo andrological examination to enable identification of reproductive function and psycho-sexual disorders.